2019
DOI: 10.3390/nu11112836
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactobacillus plantarum TWK10 on Exercise Physiological Adaptation, Performance, and Body Composition in Healthy Humans

Abstract: Probiotics have been rapidly developed for health promotion, but clinical validation of the effects on exercise physiology has been limited. In a previous study, Lactobacillus plantarum TWK10 (TWK10), isolated from Taiwanese pickled cabbage as a probiotic, was demonstrated to improve exercise performance in an animal model. Thus, in the current study, we attempted to further validate the physiological function and benefits through clinical trials for the purpose of translational research. The study was designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
98
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(108 citation statements)
references
References 47 publications
7
98
0
1
Order By: Relevance
“…Similarly to our observation, it has been reported that Lactobacillus plantarum TWK10 increases muscle mass and promotes type I fibers (slow muscle) in murine gastrocnemius muscle [31]. Moreover, TWK10 has shown potential as an ergogenic aid to improve aerobic endurance performance via physiological adaptation effects in amateur runners and healthy humans [32,33].…”
Section: Discussionsupporting
confidence: 89%
“…Similarly to our observation, it has been reported that Lactobacillus plantarum TWK10 increases muscle mass and promotes type I fibers (slow muscle) in murine gastrocnemius muscle [31]. Moreover, TWK10 has shown potential as an ergogenic aid to improve aerobic endurance performance via physiological adaptation effects in amateur runners and healthy humans [32,33].…”
Section: Discussionsupporting
confidence: 89%
“…Our review of the literature found eleven studies investigating the ergogenic effect of probiotic supplementation (133-142, 147) ( Table 4). Common probiotic bacteria used were strains of Lactobacillus or Bifidobacterium (133,134,(136)(137)(138)(139)147). Additional strains tested included those belonging to species Bacillus subtillis (140) or Bacillus coagulans (135), Veillonella atypica (141), or even yeast Saccharomyces boulardii (142).…”
Section: The Effect Of Probiotic Supplementation On Athlete Health Anmentioning
confidence: 99%
“…In addition to performance variables, many of these studies investigated effects on body composition and inflammation. Again, results were mixed, with some studies reporting significant effects of supplementation on outcomes such as fat mass and muscle mass (132,133) or inflammatory markers (133,137,139,141,147), though results were often mixed with some biochemical markers showing no significant effect of probiotic treatment and some studies showing no significant effects at all on these outcomes (134,142). However, as none of these variables were analyzed, further research is necessary to determine the mechanism of the effects as well as whether the same effects are seen in humans.…”
Section: The Effect Of Probiotic Supplementation On Athlete Health Anmentioning
confidence: 99%
“…In our previous study, the Bifidobacterium longum (OLP-01) isolated from a weightlifting gold medalist found that, not only help in fatigue indicators, but also significantly increased 1.77-3.37-fold exercise to exhaustive time by 1X, 2X and 5X dose OLP-01 supplementation for four weeks, in addition, it also has a significant increase in forelimb grip, although there is no significant difference in muscle mass [16]. Lactobacillus plantarum (TWK10) supplement not only improves exercise performance and increases muscle mass in mice [15], but also increased endurance performance and elevated blood glucose concentration following exercise-to-exhaustion after six weeks of high dose (1 × 10 11 CFU) TWK10 supplementation in untrained healthy male adults [41]. Four weeks of SA-03 supplementation significantly increased the time from swimming endurance to exhaustion in mice ( Figure 2) and increased forelimb grip (Figure 3).…”
Section: Discussionmentioning
confidence: 99%